Identification and characterization of 17 novel polynucleotide microsatellite markers in Ocypode stimpsoni (Decapoda: Ocypodidae) - Ha Yeun Song; Young Ji Choi; Dea-Sung Lee; Hyun Ki Choi; Kyung Min Choi; Kang-Yeol Yu; Namki Cho; Seungki Lee (BMC Research Notes)
Abstract Objective The ghost crab Ocypode stimpsoni (Decapoda) is designated as a protected marine species in Korea due to its declining population. In this study, we successfully identified 17 microsatellite markers for O. stimpsoni through next-generation sequencing. Results Out of the 63 loci examined, 26 were effectively amplified in a sample of 100 individuals. These 17 loci, comprising four tri-nucleotide and 13 tetra-nucleotide repeats, exhibited a range of 4 to 26 alleles per locus (with an average of 14.1 alleles) across 100 samples from three O. stimpsoni populations. The mean observed and expected heterozygosities were calculated to be 0.885 and 0.836, respectively. These 17 newly identified polymorphic microsatellite loci hold valuable utility for investigating the genetic structure and diversity of this protected marine species.